Optimal design of a composite active aeroelastic wing - Perera, Melanie (Cranfield University, 2011)
The primary aim of this research was to design a Seamless Aeroelastic Wing (SAW) structure applicable to a lightweight Unmanned Aerial Vehicle (UAV). Therefore the study focused on optimal design of a SAW structure by utilising the maximum aeroelastic beneficial effect. Although similar to the Active Aeroelastic Wing (AAW) and relevant to the Flapless Air Vehicle Integrated Industrial Research (FLAVIIR), the major difference from them is that a SAW will function as an integrated one piece lifting and control surface. It is designed to produce a desirable wing camber for control by deflecting a hinge-less flexible trailing edge (TE) part instead of a traditional control surface. Attention was firstly paid on the design of a hinge-less flexible trailing edge control surface and the actuation mechanism applicable for a light-weight aircraft (UAV). The proposed mechanism in the SAW TE section has two innovative design features: an open sliding TE and a curved beam and disc actuation mechanism. This type of actuated TE section allows for the SAW having a smooth camber change in a desirable shape with minimum control power demand. This design concept has been simulated numerically and its feasibility has been demonstrated by a test model. The wing structure for a small scale UAV is likely to be over designed in terms of strength, stiffness and weight due to manufacturing constraints. For the optimal wing design, the investigation was conducted in two stages. In the first stage, effort was made to design and model an optimised composite wing box for a minimum weight and maximum flutter speed. Both analytical and numerical methods were used for structural stress, vibration and aeroelastic analyses. In the second stage, the study focused on integrating the TE actuation mechanism with the optimised wing box for detailed understanding of the structure. A finite element analysis was conducted to simulate the SAW TE to ensure that structural strength requirements were satisfied. Furthermore, a study was carried out on the structural dynamic behaviour of the SAW TE section under the aerodynamic pressure to demonstrate its dynamic stability. Hence, the outcome of this research shows that a feasible SAW design for a UAV can be achieved.